The Role of Workplace Spirituality in Outstanding Performance: AnPilot Study for Opinions of A Sample of Faculty Members at the College ofAdministration and Economics - University of Fallujah - Huossein, Barazan Ali; Ghareeb, Ahmed Majeed (Indonesian Journal of Law and Economics Review, 2025)
General Background: In the modern academic and organizational context, workplace spirituality has emerged as a crucial factor influencing employee behavior and institutional success. Specific Background: Within Iraqi higher education, institutions face challenges in fostering performance excellence, making it necessary to explore nontraditional motivators such as spirituality at work. Knowledge Gap: Despite its growing importance, limited empirical evidence exists regarding how the dimensions of workplace spirituality—meaningful work, sense of community, and alignment between individual and organizational values—affect outstanding performance in Iraqi academic environments. Aims: This study aims to examine the role of workplace spirituality in achieving outstanding performance among faculty members of the College of Administration and Economics, University of Fallujah. Results: Using a descriptive method and data from 76 respondents, the study found significant positive correlations and effects between all dimensions of workplace spirituality and outstanding performance, with alignment between individual and organizational values showing the strongest impact. Novelty: This research is one of the first to empirically validate the influence of workplace spirituality on performance within Iraqi higher education institutions. Implications: The findings highlight the necessity for universities to integrate spiritual and ethical dimensions into organizational culture to enhance employee engagement, collaboration, and overall institutional performance. Highlight : Workplace spirituality significantly correlates with outstanding performance at the University of Fallujah. Meaningful work and value alignment are the most influential dimensions. Spirituality fosters belonging, satisfaction, and collaboration for superior results. Keywords : Workplace Spirituality, Outstanding Performance, Meaningful Work, Sense of Community, Alignment Between Individual and Organizational Values